Si-Ni-San reduces lipid droplet deposition associated with decreased YAP1 in metabolic dysfunction–associated fatty liver disease. (6th April 2023) - Zheng, Kangning; Zhou, Wenhan; Ji, Jingmin; Xue, Yu; Liu, Yiwei; Li, Caige; Zhang, Zhiqin; Lu, Junlan; Shi, Xinli; Li, Yongmin
Abstract: Ethnopharmacological relevance: Metabolic dysfunction-associated fatty liver disease (MAFLD) is the most common chronic liver disease worldwide. However, its complex pathogenesis and lack of effective drugs for treating it present significant challenges. Si-Ni-San (SNS) is one of the representative formulas for treating patients with MAFLD in traditional Chinese medicine (TCM) clinics. According to our previous work, SNS reduces lipid droplet (LD) deposition in livers of mice with MAFLD. Aim of the study: To elucidate the mechanism of SNS in reducing LD deposition in MAFLD. Materials and methods: First, LD areas were detected with Oil red O staining in HepG2 cells induced by oleic acid (OA). Cell Counting Kit-8 (CCK-8) assay was used to test cell viability after treatment with different concentrations of SNS serum. The expression of Yes-associated protein 1 (YAP1) was monitored by Western blot. Second, C57BL/6 mice were fed a high-fat diet (HFD) for 12 weeks and gavaged with SNS decoction during the 11th and 12th weeks. Then, the weight of the body and the liver was examined. LD numbers and their locations in the liver were detected by triglyceride (TG) assay and hematoxylin and eosin staining (H&E). The expression levels of YAP1 and perilipin2 (PLIN2) were detected using Western blot and immunohistochemistry (IHC) in liver tissues. Finally, active ingredients of SNS decoction and SNS serum were identified by liquid chromatography-mass spectrometry (LC-MS). Finally, molecular docking was performed between the compounds in SNS and YAP1 to analyze their active interaction. Results: Cellular experiments showed that SNS serum reduced LD vacuoles and YAP1 expression in OA-induced HepG2 cells. Animal experiments confirmed that LD vacuoles, PLIN2 expression (3.16-fold), and YAP1 expression (2.50-fold) were increased in the HFD group compared with the normal diet (ND) group. SNS reduced LD vacuoles, TG content (0.84-fold), PLIN2 expression (0.33-fold), and YAP1 expression (0.27-fold) compared with the normal saline (NS) group in Yap1 Flox mice with MAFLD. In SNS, baicalein-6-glucuronide, desoxylimonin, galangin-7-glucoside, glycyrrhizic-acid, licoricesaponin-K2, and nobiletin showed a high binding effect with YAP1. Knockout of hepatocyte YAP1 reduced LD vacuoles, TG content (0.40-fold), and PLIN2 expression (0.62-fold) in mice. Meanwhile, SNS reduced LD vacuoles, TG content (0.70-fold), and PLIN2 expression (0.19-fold) in Yap1 LKO mice with MAFLD. The effect of SNS in reducing TG and PLIN2 was diminished in Yap1 LKO mice compared with Yap1 Flox mice. Conclusion: SNS reduced LD deposition and YAP1 expression in MAFLD liver cells both in vivo and in vitro. YAP1 was highly expressed in livers with MAFLD, and knockout of hepatocellular YAP1 reduced LD deposition in mice. SNS reduced LD deposition associated with decreased YAP1 in MAFLD liver cells. Graphical abstract: Image 1